Full thickness burn after Thai herbal hot compress massage ball therapy. Issue 2 (April 2021) - Cheung, Lok Ka; Osei-Kuffour, Denise; Drake, Paul J.H.
Highlights: Burns. Hot compress. Massage. Thermal burns. Abstract: Thermal burns from therapeutic modalities have previously been reported in East Asian and Australasian literature. However, there is a paucity of similar cases reported in Western populations of burns secondary to therapeutic modalities and given the increasing popularity of such therapies, we think it important to highlight some of the potential risks. Here we present a case of full thickness burn to the right shoulder in an adult male requiring tangential excision and skin grafting after receiving Thai Herbal Hot Compress Massage Ball Therapy four days earlier. We aim to raise awareness of thermal burns secondary to such therapeutic modalities and remind clinicians and therapists the proportional time–temperature relationship in such low-moderate burns causing significant burn injuries. Traditional or alternative medical practitioners should be aware and trained in the first aid of burns and remain highly vigilant to the possibility of contact burns in these patients. Future work will involve undertaking a telephone survey of massage therapists to understand their practices regarding training in the identification, prevention and first aid management of burns.